Avaliação histopatológica e bioquímica da ínjúria hepática experimental induzida pelo tratamento crônico de ratos com o D-Limoneno. - Ramos, Carlos Alberto Fernandes (2010)
This study aimed to evaluate the hepatotoxic potential of d-limonene - a component of volatile oils extracted from citrus plants. The preclinical research was conducted in an animal model (rats) with emphasis on histopathological and immunopathological studies for determination of tissue lesions and understanding of their pathogenic mechanisms. Sixty-three Wistar rats were randomly divided into eight groups. In addition to the control groups (untreated or receiving only vehicle), experimental groups were treated for 30 or 45 days with d-limonene at doses of 25 mg/kg/day and 75 mg/kg/day. Two other groups (satellites) were followed for 60 days, receiving the substance only in the first 30 days in the same dosages of previous groups. To other rats group was given 20% ethanol in low doses (3.5 ml/kg/day), expecting to compare the alcohol toxic effects with those of d-limonene. Scores were statistically analyzed using Kruskal-Wallis and ANOVA with Tukey post-test (p <0.05). Biochemical researches showed no statistically significant elevations in levels of aspartate aminotransferase (AST) and alkaline phosphatase (ALP), while changes in alanine aminotransferase (ALT) were significant in the animals group treated with the higher dose of d-limonene. Histological analysis revealed the occurrence of inflammatory liver injury, parenchymal, chronic, small or medium intensity in the group treated with d-limonene. Hydropic degeneration, hepatocytic necrosis, hyperplasia of Kupffer cells, microvesicular steatosis and incipient fibrosis were the microscopic changes that variously accompanied the local inflammatory response. Immunopathological studies indicated that liver injury was due in part to the presence of T lymphocytes (CD3 +) cytotoxic (CD8 +), reinforcing the theories advocated by several authors that cellular immunity participates in drug-induced hepatotoxicity. The complex pathogenic mechanism is probably initiated by the generation of secondary reactive substances to the oxidative metabolism of drugs. Such metabolites can combine with macromolecules, damaging structures and cellular functions and forming immunogenic haptens. Hyperplastic Kupffer cells also contribute to the process of hypersensitivity, with the elaboration of cytokines. Ito cells are stimulated in the perisinusoidal spaces being transformed into myofibroblasts, matrix-substance producers, starting fibrogenic processes. In this experimental model with d-limonene, perisinusoidal thin collagen fibers were observed only with specific staining techniques (picrosirius red), indicating early fibrosis, in isolated outbreaks, associated with more significant inflammatory lesions.